THE EFFECT OF FINANCIAL LITERACY AND FINANCIAL TECHNOLOGY ON FINANCIAL INCLUSION IN GENERATION Z OF CURUG VILLAGE, KLARI DISTRICT, KARAWANG REGENCY - Shintia Noviyanti; Dedi Mulyadi; Santi Pertiwi Hari Sandi (SEAN Institute, 2022)
This study aims to determine and analyze the effect of Financial Literacy and Financial Technology variables on Financial Inclusion in Generation Z in Curug Village, Klari District, Karawang Regency. This Study uses a descriptive verification method with a quantitative approach and the research data used are primary data. The population in this study were 1000 people aged 17-25 years old. The sampling technique used is the proportional sampling method and uses the table formula from Isaac and Michael in order to obtain 258 respondents. The analytical method used is path analysis. The data was processed statistically with the t test model. The results of this study indicate that partially the variables of Financial Literacy and Financial Technology have a significant effect on Financial Inclusion in Generation Z in Curug Village, Klari Distruct, Karawang Regency